Abundance of selected bacterial groups in healthy calves and calves developing diarrhea during the first week of life: Are there differences before the manifestation of clinical symptoms? - Schwaiger, Karin; Storch, Julia; Bauer, Christoph; Bauer, Johann (Frontiers in Microbiology, 2022)
Background Diarrhea is still the most common and economically most significant disease of newborn calves. Objective Analysis of the development of selected bacterial groups in the feces of neonatal calves and its significance regarding diarrhea. Animals A total of 150 newborn Simmental calves reared in 13 Bavarian farms were included in the study. Methods Fecal samples of calves taken at 0/6/12/24/48/72/168 hours (h) since birth were analyzed qualitatively and quantitatively for aerobic and anaerobic bacteria, such as Enterobacteriaceae, E. coli, enterococci, and lactobacilli, using cultural, biochemical, and molecular-biological methods. Concurrently, the health status of the animals was recorded. The bacterial levels of healthy and diarrheic animals were compared using statistical methods. In addition, feces samples from calves that developed diarrhea were examined by ELISA for the presence of rotaviruses, coronaviruses, E. coli F5, and Cryptosporidium (Cr.) parvum. Results Fifty-seven out of 150 calves (37.3 %) that were examined developed diarrhea within the first week of life. In the feces of calves with diarrhea on day 1 of life, the levels of aerobes, Enterobacteriaceae, and E. coli were significantly increased (p < 0.05), while no significant differences in enterococci and lactobacilli were found. In animals with the onset of diarrhea on day 2 after birth, the load of lactobacilli was significantly reduced up to 24 h before the manifestation of clinical symptoms compared to healthy calves. For enterococci, this was only the case on the day of the onset of diarrhea. In addition, the ratios of aerobic and anaerobic bacteria, Enterobacteriaceae or E. coli to lactobacilli, of calves with diarrhea starting on day 2 after birth are significantly higher than those of healthy calves. The detection frequency of specific pathogens in diarrheic calves increased over the first week of life. Conclusion The results suggest that the incidence of neonatal diarrhea in calves is favored by low levels of lactobacilli in the feces. From this, the hypothesis can be derived that, in addition to an optimal supply of colostrum, the earliest possible administration of lactobacilli might reduce neonatal diarrhea in calves. However, this must be verified in a subsequent feeding experiment.